2006
DOI: 10.5575/geosoc.112.459
|View full text |Cite
|
Sign up to set email alerts
|

Fission track ages of tuffaceous sandstone from the Toki Lignite-bearing Formation of the Mizunami Group in the Tono district, Gifu Prefecture, central Japan

Abstract: The depositional age of the Toki Lignite-bearing Formation of the lowermost part of the Miocene Mizunami Group, which is distributed in the southeastern part of Gifu Prefecture, central Japan, has been investigated by fission track FT dating and petrographic description of four tuffaceous sandstones.An investigation of the refractive indices of plagioclase suggests that the tuffaceous sandstones are a mixture of andesitic tuff and granitic detritus. Two age populations, -Ma early Miocene and -Ma late Cretaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…After passing the AFT PAZ, the t–T path in each sample (Figure ) became low‐gradient and then attained the same temperature level as that in the present day at 30–20 Ma, indicating that the Toki granitic body was exposed to the surface prior to this time. The depositional age of the Mizunami Group overlying the Toki granite corresponds to the period of 20–18 Ma (Sasao et al, ). These temporal relations can explain the time sequence from the exposure of the Toki granite to the formation of the Mizunami Group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After passing the AFT PAZ, the t–T path in each sample (Figure ) became low‐gradient and then attained the same temperature level as that in the present day at 30–20 Ma, indicating that the Toki granitic body was exposed to the surface prior to this time. The depositional age of the Mizunami Group overlying the Toki granite corresponds to the period of 20–18 Ma (Sasao et al, ). These temporal relations can explain the time sequence from the exposure of the Toki granite to the formation of the Mizunami Group.…”
Section: Discussionmentioning
confidence: 99%
“…The Nohi rhyolite, a pyroclastic flow deposit, formed prior to the intrusion and emplacement of the Toki granite (zircon CHIME age 85 AE5 Ma and allanite CHIME age 86 AE7 Ma; Suzuki, Nakazaki, & Adachi, 1998). The Miocene Mizunami Group, which has an age of 20-18 Ma (Sasao, Iwano, & Danhara, 2006), is composed of fluvial, lacustrine, and neritic sediments (Itoigawa, 1974(Itoigawa, , 1980. The Toki granite is unconformably overlain by the Mizunami Group (Itoigawa, 1974(Itoigawa, , 1980.…”
Section: Toki Granite In the Tono Districtmentioning
confidence: 99%
“…Zircon fission track results suggest that the group was deposited in the early to middle Miocene (Kobayashi 1989;Sasao et al 2006Sasao et al , 2011, although no data have been reported for the Oidawara Formation. Paleomagnetic polarity and marine microfossil data, including biostratigraphic data for planktonic foraminifera, radiolaria, and diatoms, constrain the age of the shallow marine sediments within the Mizunami Group (Kawamura et al 2011, and references therein).…”
Section: Geological Settingmentioning
confidence: 84%
“…) is younger than the depositional age of the Mizunami Group (20–15 Ma; Itoigawa ; Sasao et al . ). Therefore, at present, there are no candidate volcanic sources for the supply of volcanic materials to the Mizunami Basin.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, Sasao et al . () reported that tuffaceous sandstones in the lowermost part of the Mizunami Group are composed of andesitic tuff and clastic sediments, which were likely derived from granitic rocks, indicated by their heavy mineral and plagioclase compositions.…”
Section: Introductionmentioning
confidence: 99%